PENGARUH KOMPENSASI, LINGKUNGAN KERJA, DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA CV. PASSIFIC AMI ANTON KLATAKAN KABUPATEN SITUBONDO - Randika Fandiyanto (Growth, 2021)
Human Resources is one of the important factors in an organization or company. Human Resources must be managed properly to increase the effectiveness and efficiency of the organization. Therefore, it is necessary to have a company function, namely human resource management.The results of the multiple linear regression analysis equation are: Y = 1,744 + 0.366 X1 + 0.697 X2+ -0.602 X3 + e.show that in the Compensation variable, the value of tcount is 4.819 > ttable 2.032 and a significant value of 0.000 <0.05.In the Work environment variable, the tcount value is 10.169 < ttable 2.032 and a significant value is 0.00 > 0.05,so Ho is accepted and Ha is rejected independently (partial).The Organizational culture variable has no significant effect on job satisfactiona tcount of -1.310 < ttable 2.032 and a significant value of 0.199 > 0.05together (simultaneously) have a significant influence on job satisfaction.The results of the calculation of the dominant test can be concluded that the value of the compensation variable (X1) is 4.819 while the value of the work environment variable (X2) is 10.169 and organizational culture (X3) is -1310, then H3 states that the work environment variable has the most dominant influence on employee job satisfaction is accepted.